PENGAKUAN KEDUDUKAN ANAK DI LUAR PERKAWINAN DALAM KAJIAN HUKUM POSITIF - Noviyanti Wulandari Sitepu; Tan Kamello; Hasim Purba; Dedi Harianto (USU LAW JOURNAL, 2014)
ABSTRACT Legal consequence caused by a legal marriage is that the child, born from it, will be a legitimate child who has civil law relationship with the parents. On the other hand, an illegal marriage will not have any ralationship with legal consequence. A child from an illegal marriage will become the target of social law caused by the biological mother and the genetic father. The position of as  child plays an important part in a marriage although the father may not recognize his child when the latter comes from an illegal marriage. The recognition of a child’s position is merely as a ‘recognized child’ (natuurlijk erkendkind) and not as a legitimate child (wettig kind) without being followed by a legal marriage. It can be formulated some problems as followed : 1) how about the background of a child’s position from an illegal marriage in the study of positive law, 2) how about the recognition of an illegitimate child’s position in the study of positive law, and 3) how about the implementation of an illegitimate child’s civil right in the study of positive law. Research better way to solved problem or to find answer from principal deduce and then systematic planning. Methodology is a logic based from scientific research. From the result of the research, it can be concluded that for the case which needs the provision of a marriage, judges do not need to refer to the Ruling of the Constitusional Court No. 46/PUU-VIII/2010. They only needs to examine the completesness of evidence and hears witnesses who are prensented as applicants. For the case of recognizing an illegitimate child, judges refer to the Ruling of the Constitusional Court No. 46/PUU-VIII/2010 as the consideration for the sake of the child. Keywords : Illegitimate Child, Recognition of Illegitimate Child, Civil Right of Illegimate Child.